Repricing executive stock opition in a down market - Saly, P.Jane (Journal of Accounting and Economics, 1994)
This paper analyzes the repricing of employee stock options after market-wide crash. The model identifies sufficient conditions for renegotiation to be optimal and for optimal compensation to be a fixed salary plus stock options. Empirical results support the renegotiation prediction. Stock opition grants increase in both number and value after the 1987 crash. Firms with underwater options grant significantly more options post-crash than pre-crash, whereas firm with in-the-money options don't. Furthermore, firms suffering the largest impact from the crash are the most likely to increase grants after the crash.